Pengaruh Kebiasaan Sarapan terhadap Kejadian Anemia pada Remaja Putri: Literature Review - Nanda Indah Permatasari; Diah Mulyawati Utari (Malahayati Nursing Journal, 2025)
ABSTRACT For adolescents, meeting nutritional needs by maintaining a regular breakfast habit is highly important. Breakfast is essential for adolescents as it supports overall health, cognitive performance, and academic achievement. Inadequate dietary intake is one of the contributing factors to the development of anemia. Anemia is a common nutritional problem during adolescence, characterized by decreased hemoglobin levels (Hb 12 g/dL). This condition is more prevalent among adolescent girls due to increased iron requirements associated with growth and the replacement of iron lost during menstruation. To examine the effect of regular breakfast consumption on the incidence of anemia among adolescent girls. This study employed a literature review method to analyze the effect of breakfast consumption on the incidence of anemia among adolescent girls. Three databases were used to search for relevant articles: PubMed, Scopus, and Google Scholar, following specific inclusion and exclusion criteria. The inclusion criteria consisted of primary research articles that examined breakfast and anemia among junior and senior high school adolescent girls, published between 2015 and 2025, available in full text, open access, written in English or Indonesian, and sourced from Indonesian journals indexed by SINTA within the search year. For Google Scholar, only the first ten pages (approximately the first 100 articles) were considered. The exclusion criteria included review articles (literature or systematic reviews), grey literature, and unpublished studies. The selected articles were identified and analyzed using the PRISMA flowchart method. A total of eight articles were analyzed in this study. Seven out of the eight articles demonstrated that breakfast habits were significantly associated with the incidence of anemia among adolescent girls, while one article revealed a significant relationship between breakfast habits and nutritional status. Adolescent girls who frequently skip breakfast are more likely to experience anemia. In addition to developing the habit of having breakfast regularly, attention to adequate nutrient intake is also essential for adolescent girls to prevent the occurrence of anemia. Keywords: Breakfast, Anemia, Adolescent Girls.  ABSTRAK Bagi remaja, pemenuhan kebutuhan zat gizi dengan membiasakan mengonsumsi sarapan secara rutin merupakan hal yang sangat penting. Sarapan dibutuhkan oleh remaja untuk kesehatan dan kinerja kognitif serta akademik. Konsumsi makanan yang tidak mencukupi menjadi salah satu yang menyebabkan terjadinya anemia. Anemia merupakan salah satu masalah gizi yang umum terjadi pada masa remaja yang ditandai dengan penurunan kadar haemoglobin (Hb 12 g/dl). Kondisi ini lebih rentan dialami remaja putri karena kebutuhan akan zat besi yang meningkat akibat proses pertumbuhan dan mengganti kehilangan zat besi selama menstruasi. Mengengetahui pengaruh sarapan terhadap kejadian anemia pada remaja putri. Penelitian tersebut menggunakan metode literature review dalam analisis pengaruh sarapan terhadap kejadian anemia pada remaja putri. Ada tiga database yang digunakan untuk menelusuri artikel yaitu PuBmed, Scopus dan scholar dengan kriteria inkulsi dan kriteria eksklusi. Kriteria Inklusinya yaitu artikel primer yang menganalisis sarapan dan anemia pada remaja putri Tingkat SMP dan SMA, terbit tahun 2015-2025, full text, open access, artikel dari jurnal Indonesia berindeks sinta di tahun pencarian, berbahasa Ingris dan Indonesia dan artikel dari google scholar berasal dari 10 halaman pertama (100 artikel awal). Kriteria ekslusi dalam menentukan artikel yaitu berjenis literature atau systematic review, grey literature dan artikel tidak di publikasi. Artikel yang terpilih diidentifikasi dan dianalisis menggunakan metode PRISMA Flowchart. Ada 8 artikel yang dianalisi dalam penelitian tersebut. Dimana 7 dari 8 artikel menunjukkan kebiasaan sarapan signifikan berhubungan dengan kejadian anemia pada remaja putri sedangkan satu artikel lainnya menunjukkan kebiasaan sarapan berkaitan signifikan dengan status gizi.  Remaja putri yang terbiasa melawatkan waktu sarapan akan mengalami anemia. Selain membiasakan sarapan secara rutin atau selalu sarapan, ada faktor asupan yang dapat diperhatikan oleh remaja putri agar kejadian anemia dapat dihindari.  Kata Kunci: Sarapan, Anemia, Remaja Putri.